1986
DOI: 10.1055/s-2008-1052503
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem Auditory Evoked Potentials in Fullterm and Preterm Newborns with Hyperbilirubinemia and Hypoxemia

Abstract: Brainstem auditory evoked potentials (BAEP) were studied in 93 newborns (49 preterm and 44 fullterm) admitted to the neonatal intensive care unit. One group of 42 infants (28-42 wk CA) were considered at low risk for perinatal complications and served to establish the normal ranges of the BAEP parameters (wave I peak latency and wave I-V interwave interval). Two groups of high risk infants were studied during or shortly following clinically significant hyperbilirubinemia (31 infants) or hypoxemia (20 infants).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 8 publications
0
15
0
1
Order By: Relevance
“…The authors suggested that this was due to poorly oxygenated tissue as a result of reduced blood flow as a consequence of thrombosis and/or of anemia-induced diminished oxygen-carrying capacity. Prolonged ABR wave latencies have also been observed in post-hypoxemic preterm and full-term neonates [16].…”
Section: Introductionmentioning
confidence: 92%
“…The authors suggested that this was due to poorly oxygenated tissue as a result of reduced blood flow as a consequence of thrombosis and/or of anemia-induced diminished oxygen-carrying capacity. Prolonged ABR wave latencies have also been observed in post-hypoxemic preterm and full-term neonates [16].…”
Section: Introductionmentioning
confidence: 92%
“…For BAER studies in NICU term babies, there are previous reports in conventional BAER, mainly related to hypoxia-ischemia and hyperbilirubinemia (Akinpelu et al, 2013;Hecox et al, 1981;Newton, 2001;Streletz et al, 1986;Wilkinson and Jiang, 2006). So far, there are very few reports on MLS BAER in term babies, mainly in those who had perinatal hypoxia-ischemia (Jiang et al, 2003(Jiang et al, , 2010.…”
Section: Discussionmentioning
confidence: 96%
“…The most common criterion for asphyxia was a 1-or 5-min Apgar score of less than 6; however, some investigators used more stringent criteria and included only those with lower Apgar scores who also needed to be intubated, ventilated, or both for varying periods of time after birth. Statistical controls for conceptional age were used in only one study with positive findings (Streletz et al, 1986). Statistical controls for conceptional age were used in only one study with positive findings (Streletz et al, 1986).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Cox et al (1984) and Ito (1984) reported no relation in their samples. Streletz et al (1986), who used acidosis as one of the defining criteria for his asphyxiated group, reported more peripheral ABR abnormalities (prolonged latencies of Wave I) among his asphyxiated group.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation